Legal Force of Decision of Consumer Dispute Resolution Agency (BPSK) on Rejection of Life Insurance Claims - Hutabalian, Maslon; Nadirah, Ida (Rechtsvinding, 2025)
Claim rejection by life insurance companies is one form of consumer dispute that often occurs in the financial services sector. To ensure legal protection for consumers, the Consumer Dispute Resolution Agency (BPSK) is authorized to resolve disputes outside the court quickly, simply, and cheaply. This study aims to analyze the legal force of BPSK decisions on life insurance claim rejection disputes and the extent of their effectiveness in practice. The method used is a normative legal approach with an analysis of laws and regulations, BPSK decisions, and related court decisions. The results of the study indicate that BPSK decisions have final and binding legal force if no objections are filed with the court within the specified time period. However, the effectiveness of its implementation is often hampered by institutional weaknesses and overlapping authority with other financial services sector dispute resolution institutions.